Mixed medullary-papillary thyroid carcinoma with mixed lymph node metastases: A case report - Guerreiro, V (2021)
Mixed medullary-follicular-derived carcinoma is a very rare event. It is extremely important to make the correct diagnosis, due to prognostic and treatment implications. A genetic study of these patients is advisable to exclude the presence of MEN 2.